Public opinion towards the roles of the military in politics - Bacaoco, Jeemon Rey A.; Tabernilla, Piologo A. (2011.)
The study has 200 respondents all from Iloilo City, randomly selected according to population in all six districts. The respondents were given a four-category questionaire to answer detailed in value statements the military's role: traditional role of the military, non-traditional roles of the military, former military in politics and military and society. This paper obtained the public's opinion through their anwers in the questionaire that employed a Likert-Scale that ranges from 1 as strongly disagree, 2 as disagree, 3 as agree and 5 as strongly agree. The result showed that the public disagrees with the military participation in politics as shown in their disagreements with the military taking over in times of presidential vacancy with 80.5 percent in the disagree scale and in former military personnel entering into politics with 80 percent on the disagree scale. But in terms of the non-traditional roles of the military, the public agrees with them, like they largely agree with the traditional ones, not seeing them as opportunities for roles in politics.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2011.
Keywords: Military -- Political participation